Process signature in machining of 316L stainless steel under dry and flood condition - Cholis, N.; Ahmad Razlan, Yusoff (Springer, 2025)
Among the various engineering materials available today, 316L stainless steel stands out as the preferred choice for industrial structural applications. Its exceptional properties make it suitable for use in automobiles, atmospheric distillation plants, aircraft and marine systems. Currently, limited sources are available because few studies have been conducted on the process signature of 316L stainless steel during turning operations with a carbide tool in both dry and flood cutting. The aim of this study was to investigate the influence of machining parameters on the turning process of 316L stainless steel under different lubrication conditions and to apply the concept of process signature. The experiment was conducted to machine 316L stainless steel using turning process. The machining parameters were tested at a constant cutting depth. The parameters for this experiment included cutting speed, feed rate, and cutting condition. Three different values were examined for each parameter: cutting speed, feed rate and turning machining under dry and flood machining conditions. The cutting speeds tested were 80, 100 and 110 m/min, while the feed rates were 0.10, 0.16 and 0.25 mm/rev, all with a constant cutting depth of 0.3 mm. The results clearly demonstrate that the process signature concept showing that consistent internal material stresses result in predictable material modifications when machining 316L stainless steel highlights the need for further research on residual stresses and fatigue failure.